Modelagem molecular de sensores químicos fluorescentes derivados de oximas para detecção de organofosforados - Silva, Érika Ferreira (2016)
Organophosphates (OPs) are organic compounds largely used in agriculture, as well as chemical weapons. Its use in agriculture is due to its insecticide properties. Its employment as chemical weapon is associated to the inhibition of the enzyme acetylcholinesterase, promoting the cholinergic syndrome. In this context, the quick detection of this class of compounds is crucial for an effective treatment. In this perspective, compound 1was employed for detecting the OPs, using nerve agents such as Ciclosarin, Sarin, Soman, GV, VG, VM, VX, DFP and DCP, by means of fluorescent emission. Thermodynamic and kinetic parameters, as well as spectroscopic properties of the complexes formed between the OPs and compound 1, were assessed by theoretical calculations. With the results obtained, we verified that only DCP, GV and VG emit fluorescence on solvents hexane, toluene, chloroform, DCM, methanol, acetonitrile , water and DMSO. The thermodynamic paramet ers indicate negative values for ΔG for VX for the reaction with 1, while Sarin and Ciclosarin reveal the smaller values for ΔG‡, being kinetically favorable and presenting higher reactivity.